Unusual presentation of blastic plasmacytoid dendritic cell neoplasm: Pitfalls in other hematolymphoid neoplasms - Alexis Trecourt; Brigitte Balme; Marie-Hélène Lorton; Juliette Fontaine; Pauline Desormeaux; Cédric Rossi; Jean-Noël Bastie; Ingrid Lafon; Géraldine Jeudy; Sophie Dalac; Sarah Huet; Pierre Sujobert; et al. (Elsevier, 2020)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare CD4+/CD56+ hematological malignancy with aggressive clinical course and poor prognosis. Histologically, BPDCN is characterized by a diffuse, monomorphous infiltration of cutaneous, subcutaneous, and sometimes other tissues such as lymph nodes and bone marrow, by medium-sized neoplastic cells with blastoid morphology. Typically, there is absence of lymphocytic infiltrate. Diagnosis relies on immunophenotypic expression of CD4, CD56, and the more specific markers of plasmacytoid dendritic cells CD123, CD303/BDCA2, and TCL1.We report a case of a 57-year-old man who presented a 4 cm-long solitary, erythemateous lesion on the right cheek, corresponding to a BPDCN but initially misdiagnosed as T-cell lymphoma. The case was characterized by conservation of skin appendages and a diffuse T-cell infiltrate, which strongly expressed PD1. ETV6 and MYC fluorescent in situ hydridization and next-generation sequencing were performed on this tumor.The main difficulties to diagnose BPDCN were the atypical cytology of tumor cells and their CD4 and CD43 expression, as can be seen in T-cell lymphomas. The diffuse T-cell infiltrate was also challenging. The patient is still alive 29 months after diagnosis, suggesting a potential prognostic impact of T-cell infiltration and the absence of MYC translocation. The presence of TET2 and ASXL1 mutations supporting BPDCN and reinforcing the hypothesis of a myeloid origin.